Reaching the Monophyly: Re-Evaluation of the Enigmatic Species Tenuibiotus hyperonyx (Maucci, 1983) and the Genus Tenuibiotus (Eutardigrada) - Daniel Stec; Witold Morek (Animals, 2022)
Revisions and redescriptions of taxa described in the past and that are now categorized as insufficiently diagnosed often play a crucial role in making further progress in modern taxonomy in many groups of organisms. Here we revised an enigmatic tardigrade species Tenuibiotus hyperonyx (Maucci, 1983) based on the newly discovered topotypic population from the Italian Alps. We performed an integrative analysis of morphological and genetic data in order to present an upgraded species description and elucidate its phylogenetic position. Our results enabled us to confidently place T.hyperonyx within the family Richtersiusidae, as a member of the genus Diaforobiotus. This change, together with a re-assessment of microphotographs of the Tenuibiotus willardi (Pilato, 1977) and Tenuibiotus bozhkae Pilato, Kiosya, Lisi, Inshina & Biserov, 2011 types, led to the discussion on species composition with narrative taxa amendments for the taxonomic parties involved in the proposed alteration.